Mystery Shopping: Demand-Side Phenomena in Markets for Personal Plight Legal Services - Semple, Noel (2017)
"Personal plight" is the sector of the legal services industry in which the clients are individuals, and the legal needs arise from disputes. This article proposes that competition among personal plight law firms is suppressed by three demand-side phenomena. First, consumers confront high search costs. Identifying competing law firms willing and able to provide the needed services often requires significant expenditure of temporal and psychological resources. Second, comparable price and quality information about firms is scarce for consumers. Both of these factors impede comparison shopping and reduce competitive pressure on firms. A third competition-suppressing factor is observed in tort legal service markets, where offerings are typically priced on a contingency basis. Contingency fees have relatively low salience to consumers, and this reduces consumers' willingness to negotiate and comparison-shop on the basis of price. This analysis is supported by the author's empirical research with Ontario personal plight lawyers as well as the existing literature. The article concludes by suggesting possible consequences of this analysis for regulatory policy.
Keywords: Noel Semple